2017
DOI: 10.1186/s12872-016-0466-1
|View full text |Cite
|
Sign up to set email alerts
|

The safety of introducing a new generation TAVR device: one departments experience from introducing a second generation repositionable TAVR

Abstract: BackgroundIn the evolving field of transcatheter aortic valve replacements a new generation of valves have been introduced to clinical practice. With the complexity of the TAVR procedure and the unique aspects of each TAVR device, there is a perceived risk that changing or adding a new valve in a department could lead to a worse outcome for patients, especially during the learning phase. The objective was to study the safety aspect of introducing a second generation repositionable transcatheter valve (Boston S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…High PPM rates after implantation of a Lotus Valve System compared to 1st generation TAVI has been identified as a significant drawback of the technology. [19, 20] The PPM rates in all patients in the REPRISE I and II studies were 36 and 28.6% respectively. [7, 8] Two single-center studies using the Lotus Valve System have demonstrated an incidence of new PPM of 24.1 and 39.9% in pacemaker-naïve patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High PPM rates after implantation of a Lotus Valve System compared to 1st generation TAVI has been identified as a significant drawback of the technology. [19, 20] The PPM rates in all patients in the REPRISE I and II studies were 36 and 28.6% respectively. [7, 8] Two single-center studies using the Lotus Valve System have demonstrated an incidence of new PPM of 24.1 and 39.9% in pacemaker-naïve patients.…”
Section: Discussionmentioning
confidence: 99%
“…The Lotus Valve System was designed to reduce PVL compared to 1st generation TAVI valves by using an adaptive seal. [19, 20] The occurrence of moderate or severe PVL after TAVI implantation is an independent predictor of increased short and long-term mortality rate. [9, 10, 24, 25] In the REPRISE II CE mark multicenter study where 120 patients received a Lotus Valve System, the rate of PVL at discharge was mild in 13.1% and moderate in 2% of patients.…”
Section: Discussionmentioning
confidence: 99%